The Relationship between Family Support and Health Workers with Compliance of Pregnant Women in Consuming Fe Tablets - Fajriah, Asruria Sani; Udin, Nur Alam; Sejati, Putri Eka; Effendy, Mohammad As'ad; Nursanti, Devy Putri (Universitas Muhammadiyah Semarang, 2024)
The results of Riskesdas in Indonesia in 2018 showed that the proportion of pregnant women who received iron tablets was 73.2% while those who consumed Fe were 23.8%. The compliance coverage of pregnant women is still low in consuming iron supplement tablets. The purpose of this research is toanalyzed the relationship between family support and health workers on the compliance of pregnant women in consuming Fe tablets at the Lembur Health Center in Alor Regency. Design this research is a type of quantitative research with a cross-sectional design. Respondents were taken by accidental sampling technique. With a sample of 30 people. Data analysis used the Chi Squere test. The results of the analysis using the chi squere test show that there is a relationship between family support and consumption of Fe tablets at the Alor Regency Lembur Health Center in 2022 with a P-Value of 0.012. 0.594. Efforts to increase adherence to consumption of FE tablets for pregnant women can be carried out by increasing family knowledge and awareness by conducting counseling by health workers to the community.